Improving pandemic preparedness through better, faster influenza vaccines. (4th March 2021) - Newland, Matthew; Durham, David; Asher, Jason; Treanor, John J.; Seals, Jonathan; Donis, Ruben O.; Johnson, Robert A.
ABSTRACT: Introduction . Timely availability of effective influenza vaccine will be critical to mitigate the next influenza pandemic. The mission of Biomedical Advanced Research and Development Authority (BARDA) is to develop medical countermeasures against pandemics, including influenza and other health security threats. Areas covered . Despite considerable gains in pandemic vaccine preparedness since 2009, old and new challenges threaten the pandemic influenza response capabilities of the U.S. Government: insufficient U.S.-based vaccine production, two-dose vaccination regimen, logistically complex adjuvanted formulation, and sustained surge manufacturing capacity despite no commercial market for pandemic vaccines. Although the coronavirus disease 2019 (COVID-19) pandemic has re-exposed these gaps in preparedness and response, previous investments into flexible influenza vaccine technologies proved to be critical to accelerate COVID-19 vaccine development. Expert opinion . BARDA addresses these challenges by implementing a pandemic influenza vaccine strategy with two key goals: 1) accelerating vaccine development and production (faster ) and 2) improving vaccine performance (better ). This strategy involves an end-to-end approach, including increasing manufacturing and fill-finish capacity; improving release testing speed; and funding clinical trials to improve current vaccine utilization. As demonstrated by the COVID-19 response, continued investments into this pandemic influenza vaccine strategy will further enhance the ability to respond to future emerging pandemic pathogens.